Atomic layer deposition of HfO 2 for integration into three-dimensional metal–insulator–metal devices - Assaud, Loic; Pitzschel, Kristina; Barr, Maissa K. S.; Petit, Matthieu; Monier, Guillaume; Hanbucken, Margrit; Santinacci, Lionel (Applied Physics A: Materials Science and Processing, 2017)
HfO 2 nanotubes have been fabricated via a template-assisted deposition process for further use in three-dimensional metal–insulator–metal (MIM) devices. HfO 2 thin layers were grown by Atomic Layer Deposition (ALD) in anodic alumina membranes (AAM). The ALD was carried out using tetrakis(ethylmethylamino)hafnium and water as Hf and O sources, respectively. Long exposure durations to the precursors have been used to maximize the penetration depth of the HfO 2 layer within the AAM and the effect of the process temperature was investigated. The morphology, the chemical composition, and the crystal structure were studied as a function of the deposition parameters using transmission and scanning electron microscopies, X-ray photoelectron spectroscopy, and X-ray diffraction, respectively. As expected, the HfO 2 layers grown at low-temperature (T=150∘C) were amorphous, while for a higher temperature (T=250∘C), polycrystalline films were observed. The electrical characterizations have shown better insulating properties for the layers grown at low temperature. Finally, TiN / HfO 2/ TiN multilayers were grown in an AAM as proof-of-concept for three-dimensional MIM nanostructures.
Created from Fastlane, Scopus look-up